(untitled) (RUNA, archivo para las ciencias del hombre, 2014)
Evaluadores Extranjeros Rodrigo Diaz Cruz, Universidad Autónoma Metropolitana-Iztapalapa - UAM-Izt, México Guillermo Ruben, Universdade Estadual de Campinas -UNICAMP, Brasil Silvana Darré, FLACSO, Uruguay Fernanda Bittencourt Ribeiro, Pontificia Universidade Catolica do Rio Grando do Sul - PUCRS, Brasil Denise Jardim, Universidade Federal do Rio Grande do Sul - UFRGS, Brasil Jeffrey Erbig, University of North Carolina at Chapel Hill, EEUU Oscar Chamosa, The University of Georgia, EEUU Marco Curatola Petrocch, Ponitificia Universidad Católica del Perú – PUCP, Perú Cristobal Aljovin de Losada, Universidad Nacional Mayor de San Marcos - UNMSM, Perú Evaluadores Nacionales María A. Soto, Instituto Universitario Nacional de Arte - IUNA Alexander Roig, Universidad Nacional de San Martín -UNSaM Brigida Baesa, Universidad Nacional de la Patagonia San Juan Bosco – UNPSJB Nidia Arces, Universidad Nacional de Rosario - UNR Rodolfo Cruz, Universidad Nacional de Catamarca - UNCa Silvia Ratto, Universidad Nacional de Quilmes - UNQ Florencia Roulet, Universidad de Buenos Aires - UBA Guillermina Espósito, Universidad Nacional de Córdoba - UNC Walter Delrio, Universidad Nacional de Río Negro – UNRN